2011
DOI: 10.1111/j.1540-8175.2010.01301.x
|View full text |Cite
|
Sign up to set email alerts
|

A Patient Selection Score for Cardiac Resynchronization Therapy

Abstract: Patients with a PSS >4 are the most likely to respond to CRT. Using this score system, a PSS score >4 can predict the probability of a CRT response up to 88% in patients with heart failure and a wide QRS duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
4
5
0
Order By: Relevance
“…The LBBB was traditionally a strong predictor of electrical LV discordance in numerous large trials [7,[31][32][33][34]. Our results are consistent with the findings of the MADIT-CRT [7], RAFT [35], and REVERSERS [36] trials, which have been shown that non-LBBB patients have an increased rate of mortality due to CRT compared to those with LBBB.…”
Section: Variables Associated With the Risk Of All-cause Mortality Ansupporting
confidence: 89%
“…The LBBB was traditionally a strong predictor of electrical LV discordance in numerous large trials [7,[31][32][33][34]. Our results are consistent with the findings of the MADIT-CRT [7], RAFT [35], and REVERSERS [36] trials, which have been shown that non-LBBB patients have an increased rate of mortality due to CRT compared to those with LBBB.…”
Section: Variables Associated With the Risk Of All-cause Mortality Ansupporting
confidence: 89%
“…The LBBB was traditionally a strong predictor of electrical LV discordance in numerous large trials [7,[31][32][33][34]. Our results are consistent with the findings of the MADIT-CRT [7], RAFT [35], and REVERSERS [36] trials, which have been shown that non-LBBB patients have an increased rate of mortality due to CRT compared to that in those with LBBBs.…”
Section: Variables Associated With the Risk Of All-cause Mortality Ansupporting
confidence: 90%
“…In this study, considering these factors, atrial size is a more reliable indicator of LA function. Although the mechanism remains uncertain, the larger LA size is associated with pulmonary hemodynamic alterations and LA dilatation dysfunction [7,34,39,41,42].…”
Section: Variables Associated With the Risk Of All-cause Mortality Anmentioning
confidence: 99%
“…The LBBB was traditionally a strong predictor of electrical LV discordance in numerous large trials [7, [31][32][33][34]. Our results are consistent with the findings of the MADIT-CRT[7], RAFT [35], and REVERSERS [36] trials, which have been shown that non-LBBB patients have an increased rate of mortality due to CRT compared to those with LBBB.…”
Section: Variables Associated With the Risk Of All-cause Mortality Ansupporting
confidence: 89%
“…In this study, considering these factors, atrial size is a more reliable indicator of LA function. Although the mechanism remains uncertain, the larger LA size is associated with pulmonary hemodynamic alterations and LA dilatation and dysfunction [7, 34,39,41,42].…”
Section: Variables Associated With the Risk Of All-cause Mortality Anmentioning
confidence: 99%